The approach to long-term training in all-round karate, encompassing technical, tactical, and competitive aspects - Akopyan A.V. ,; Shakhov A.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to creating a plan for sustained technical, tactical, and competitive training in the comprehensive discipline of karate. Methods and structure of the study. The examination of information sources and the accumulation of personal coaching experience over time, the consultation with experts, the analysis of competitive matches through video recordings, the creation of simulations, and the application of statistical methods are all part of the process. Results and conclusions. The current situation has been assessed, and a comprehensive plan for long-term technical, tactical, and competitive training in all-round karate has been formulated. This plan is based on a classification of technical and tactical moves, a system for monitoring technical and tactical preparedness, and a model profile of a Russian champion.